VALIDATING THE CONSTRUCTS OF EMPLOYEES’ COMPETENCE MODEL TROUGH CONFIRMATORY FACTOR ANALYSIS: EVIDENCE FROM NIGERIA - Sani Isah; Rashidah Mohammad Ibrahim; Fazida Karim (PT Inovasi Pratama Internasional, 2023)
In recent decades, the confirmatory factor analysis (CFA) has been embraced by several scholars in assessing the fitness of measurement model through structural equation modeling procedure. In this study, five variables namely HRM practices (recruitment and selection, training and development, performance appraisal, compensation), psychological empowerment, affective commitment, work engagement, and employee competence were applied in carrying out the CFA. Applying the CFA procedure determines the researcher’s attempt to increase the ability of latent measurement model to be more outlined and précised in drawing conclusions as well as avoiding the violation of regression assumption. It appears more efficient with the use of Cronbach Alpha, Convergent validity, Discriminant Validity and Composite Reliability in the study analysis for the researcher to apply the result for further steps. Hence, findings of this study appear to be more corresponding with the overall aim of the study. Empirically, CFA is an effective tool for ensuring the best fit of measurement model. The inability of the current analysis to carry out the CFA using individual measurement serves as a great limitation. The application of pooled CFA is certainly a key to researchers in the quest to achieve the requirement for measurement model in a study with complex constructs/items. This paper aimed at presenting to the readers particularly those at the beginning stage, the importance of applying pooled CFA in empirical studies by highlighting the findings of the current study.